Resurgence initiation and subsolidus eruption of cold carapace of warm magma at Toba Caldera, Sumatra - Adonara E. Mucek (Nature Portfolio, 2021)
Post-caldera eruptions at Toba Caldera, Sumatra, following the supereruption 74,000 years ago, sampled cooler margins of the warm magma reservoir and imply its heterogeneity, according to thermochronology analyses coupled with Bayesian statistics.